Land as culture: Discourse and narratives of land claims in postcolonial Kenya. Issue 2 (3rd April 2018) - Akoth, Steve Ouma
ABSTRACT: The most recent legal and human rights histories of postcolonial Africa straddle visions that promote United Nations-centred human rights as the basis of the new nation, and another that promotes an amalgam between culture and these UN-centred human rights. In a number of African countries, these multiple visions of rights have been most manifest in matters related to land relations and governance in the context of states that have largely retained the colonial units that attempted to align administrative boundaries with imagined cultural borders to create ethnic homelands. In Kenya, where the contested history of land reforms remains divisive, Yala Swamp in Siaya County, western Kenya provides a useful case of a tussle between the local Luo residents and Dominion Farms Limited, a US-based company that was granted user rights in 1990 to a 3, 200-hectare section of the Swamp. The Constitution of Kenya 2010 (CoK, katiba in Kiswahili), that is positioned as the moment of 'change', has described land in three categories: private (20 per cent), public (13 per cent), and community (67 per cent). This article discusses the category of community land, drawing on fieldwork in which I sought to find out how Yala residents planned to use the CoK to press for their cultural rights. This and related cases will be used to illustrate the ways in which the local community in Yala has moved beyond framing the issue or controversy of multiple postcolonial visions of rights in terms of law, ethnicity and gender, to making the connection between land and culture – something the CoK made visible. It concludes that 'culture' has become a way of objectifying claims, and widening the terms of legal conflict, thus shaping and directing these into specific claims about cultural rights, and their attendant land rights processes in postcolonial Kenya.